Temperature and anion ligand field dependence of LnCl3 (Ln = Nd, Dy, Sm) electronic absorption spectra in LiCl–KCl eutectic molten salt. (March 2023) - Moon, Jeremy; Fuller, Jon; An, Qi; Chidambaram, Dev
Abstract: A comprehensive knowledge of the coordination, bonding, and speciation of elements in molten salt mixtures is necessary to understand and predict the chemical and physical properties of the salt. Absorption spectroscopy can yield information about the chemistry of species of interest in alkali halide molten salt mixtures by revealing information about the electronic structure and transitions of those species. In this study, ultraviolet (UV), visible (vis), and near-infrared (NIR) absorption spectroscopy was used to examine changes to the electronic structure of trivalent Nd, Sm, and Dy in LiCl–KCl eutectic molten salt with changes in temperature and the anion composition of the melt. With increasing temperature, changes to spectral features suggest a distortion of the coordination complexes. Changes to lineshape with the substitution of alternative halide anions were examined and analyzed, revealing differences in the coordination for I − versus F − with the lanthanides. Gaussian peak fitting was used to show that the changes in lineshape with the progressive addition of F − anions can be explained by the superposition of a set of absorption bands from complexes with all Cl − anion ligands and a set of blueshifted absorption bands from complexes containing both F − and Cl − anion ligands. This work yields a new method to analyze and interpret change to electronic absorption spectra for f-block elements dissolved in alkali halide molten salts as well as new observations of the interactions of larger and smaller halide anions with lanthanides in Cl − -based molten salts. Highlights: Gaussian peak fitting was used to quantify changes to absorption bands. Absorption lineshape and position changes with temperature or coordination. The effects of substituting I − /F − for Cl − on the absorption spectra was studied. I − does not tend to occupy lanthanide first coordination shells. Spectral changes with the addition of F − were explained using Gaussian peak fitting.